Dynamic contrast-enhanced micro-CT on mice with mammary carcinoma for the assessment of antiangiogenic therapy response. - Eisa F; Brauweiler R; Hupfer M; Nowak T; Lotz L; Hoffmann I; Wachter D; Dittrich R; Beckmann MW; Jost G; Pietsch H; Kalender WA; et al. (European Radiology, 2012)
Objective: To evaluate the potential of in vivo dynamic contrast-enhanced micro-computed tomography (DCE micro-CT) for the assessment of antiangiogenic drug therapy response of mice with mammary carcinoma.Methods: 20 female mice with implanted MCF7 tumours were split into control group and therapy group treated with a known effective antiangiogenic drug. All mice underwent DCE micro-CT for the 3D analysis of functional parameters (relative blood volume [rBV], vascular permeability [K], area under the time-enhancement curve [AUC]) and morphology. All parameters were determined for total, peripheral and central tumour volumes of interest (VOIs). Immunohistochemistry was performed to characterise tumour vascularisation. 3D dose distributions were determined.Results: The mean AUCs were significantly lower in therapy with P values of 0.012, 0.007 and 0.023 for total, peripheral and central tumour VOIs. K and rBV showed significant differences for the peripheral (P(per)(K) = 0.032, P(per) (rBV) = 0.029), but not for the total and central tumour VOIs (P(total)(K) = 0.108, P(central)(K) = 0.246, P(total) (rBV) = 0.093, P(central) (rBV) = 0.136). Mean tumour volume was significantly smaller in therapy (P (in vivo) = 0.001, P (ex vivo) = 0.005). Histology revealed greater vascularisation in the controls and central tumour necrosis. Doses ranged from 150 to 300 mGy.Conclusions: This study indicates the great potential of DCE micro-CT for early in vivo assessment of antiangiogenic drug therapy response.Key Points: Dynamic contrast enhanced micro-CT (computed tomography) is a new experimental laboratory technique. DCE micro-CT allows early in vivo assessment of antiangiogenic drug therapy response. Pharmaceutical drugs can be tested before translation to clinical practice. Both morphological and functional parameters can be obtained using DCE micro-CT. Antiangiogenic effects can be visualised with DCE micro-CT.